2011
DOI: 10.1158/1078-0432.ccr-10-2816
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ZEB2 at the Invasion Front of Colorectal Cancer Is an Independent Prognostic Marker and Regulates Tumor Invasion In Vitro

Abstract: Purpose: Epithelial-to-mesenchymal transition (EMT) plays a pivotal role in tumor invasion and dissemination. EMT occurs predominantly at the tumor edge where it is induced by cytokines, the extracellular matrix environment, or hypoxia. In the tumor cell, it is further mediated by several transcription factors and microRNAs. The aim of this study was to explore the expression of EMT-associated genes at the invasive front in colorectal cancer and to evaluate their prognostic significance.Experimental Design: We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 33 publications
8
104
0
Order By: Relevance
“…The importance of evaluating the invasive front has been reported in several gastrointestinal malignancies [28][29][30][31]. In the present study, we examined RacGAP1 expression at the invasive front in gastric cancer and observed the association of its expression with tumor progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…The importance of evaluating the invasive front has been reported in several gastrointestinal malignancies [28][29][30][31]. In the present study, we examined RacGAP1 expression at the invasive front in gastric cancer and observed the association of its expression with tumor progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 85%
“…BRAF mutation status was analyzed by Sanger sequencing as described previously. 27 In case of discordant results, a pyrosequencing-based assay was performed, using oligonucleotide primers and conditions described previously. 28 …”
Section: Braf Mutation Analysis and Microsatellite Instability Testingmentioning
confidence: 99%
“…Furthermore, ZEB1 influenced the expression of other key proteins mediated by the Wnt signaling pathway, including membrane-type 1 matrix metalloproteinase and laminin gamma chain 2 (LAMC2) (59). Therefore, indicating that LAMC2 and all proteins mediated by the Wnt signaling pathway were implicated in the invasion and dissection of colorectal cancer cells (67). Additionally, in human meningioma tumor tissues, the expression of miR-200a was negatively associated with β-catenin and cyclin D1 (68).…”
Section: Signals Regulated By the Mir-200 Family In Cancermentioning
confidence: 99%
“…This was observed in tumorigenesis for human solid tumors, including hepatocellular carcinoma, melanoma, colon, ovarian and prostate cancer (66). Nuclear accumulation of β-catenin is linked with EMT in invasive colorectal tumors, and the association between the Wnt pathway and EMT has been investigated (67). Levels of ZEB1 expression have no influence on β-catenin/transcription factor 4 transcriptional signaling in colon cancer cell lines, although ZEB1 immunopositivity has been confirmed in non-invasive colon cancer cells and in tumor-associated fibroblasts (67).…”
Section: Signals Regulated By the Mir-200 Family In Cancermentioning
confidence: 99%
See 1 more Smart Citation